2014
DOI: 10.2500/ar.2014.5.0099
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Exhaled Nitric Oxide (FeNo) in Different Asthma Phenotypes

Abstract: Fractioned exhaled nitric oxide (FeNO) is a noninvasive marker of inflammation in asthmatic patients. FeNO can be used to monitor airway inflammation, but individual responses make tailored interventions based on FeNO difficult. The correlation between the asthma control test (ACT), FEV1, and FeNO was evaluated in this study to ascertain the correct usage of FeNO with different asthma phenotypes regarding their control, allergy, comorbidity, obesity, age, smoking status, and severity. ACT, pulmonary function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 28 publications
(43 reference statements)
3
27
1
2
Order By: Relevance
“…Taylor et al studied 895 healthy adults at age 32 years and found that men had approximately 25% higher F E NO levels than women (15.5 vs 11.6 ppb). A similar size of the sex difference has also been reported in asthmatic subjectsfor example, Al‐shamkhi et al reported that in 557 subjects with asthma from the Swedish GA2LEN study, men had 32% higher F E NO levels than women (24.0 vs 16.4 ppb). However, not all studies have been able to detect sex differences in F E NO .…”
Section: Discussionsupporting
confidence: 69%
“…Taylor et al studied 895 healthy adults at age 32 years and found that men had approximately 25% higher F E NO levels than women (15.5 vs 11.6 ppb). A similar size of the sex difference has also been reported in asthmatic subjectsfor example, Al‐shamkhi et al reported that in 557 subjects with asthma from the Swedish GA2LEN study, men had 32% higher F E NO levels than women (24.0 vs 16.4 ppb). However, not all studies have been able to detect sex differences in F E NO .…”
Section: Discussionsupporting
confidence: 69%
“…Exhaled NO originates from different sources [44][45][46]. It is secreted by epithelial cells, inducing relaxation of the smooth muscle cells in the bronchial walls.…”
Section: Discussionmentioning
confidence: 99%
“…In a prior study, Cowan DC et al used the data from 46 asthmatic patients and found that the odds ratio of having a steroid response versus having no steroid response for high eNO value (>35 ppm) was 6.0. [ 19 ] In addition, we assumed the prevalence of ICS non-responders was 40% (22–60% from literature review) and that low eNO prevalence was 0.63 [ 20 ]. Thus, for one variable of odds ratio that equals to 6.0, a sample size of 51 total patients would be needed to provide 80% power with a 5% two-sided type I error.…”
Section: Methodsmentioning
confidence: 99%